2019
DOI: 10.3389/fimmu.2019.01432
|View full text |Cite
|
Sign up to set email alerts
|

Neddylation Facilitates the Antiviral Response in Zebrafish

Abstract: Neddylation is a type of post-translational protein modifications, in which neural precursor cell expressed developmentally downregulated protein 8 (NEDD8) is covalently conjugated to the lysine residues of target substrates. The best characterized principal substrates of neddylation are the cullin-RING ligases (CRLs). In addition, neddylation also modifies non-cullin proteins to affect gene regulation, cell survival, organ development, and stress response. However, the role of neddylation in antiviral innate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…Total RNA was isolated from EPC cells and fish tissues, including kidney, spleen and liver. Quantitative real‐time PCR (qPCR) was performed based on those methods reported previously (Jiang et al ., 2019; Yan et al ., 2017; Yu et al ., 2019). The primers for qPCR are listed in Supporting Information Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was isolated from EPC cells and fish tissues, including kidney, spleen and liver. Quantitative real‐time PCR (qPCR) was performed based on those methods reported previously (Jiang et al ., 2019; Yan et al ., 2017; Yu et al ., 2019). The primers for qPCR are listed in Supporting Information Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…NEDDylation is a process where target proteins undergo covalent attachment to ubiquitin-like molecule NEDD8 (neural precursor cell expressed, developmentally down-regulated 8) [ 77 ]. NEDDylated substrates have been implicated in cancer, DNA damage responses, transcriptional regulation, nucleolar stress signaling, apoptosis, and ubiquitin-proteasome machinery [ 9 ].…”
Section: Protein-based Ptmsmentioning
confidence: 99%
“…In contrast, the mutant (K699R) showed heightened virulence during infection in mice, highlighting the importance of NEDDylation on viral proteins and replication [ 5 ]. IRF3 and IRF7 were also identified as targets for NEDD8 conjugation [ 77 ], suggesting a direct link between the neddylation of viral proteins and viral replication inhibition. Moreover, the study established that NEDD8 deficient zebrafish larvae and adults were more susceptible to SVCV (Spring viremia of carp virus) infection than wild type [ 77 ].…”
Section: Protein-based Ptmsmentioning
confidence: 99%
“…It is reported that blocking or silencing neddylation dramatically increased spring viremia of carp virus (an ssRNA virus that causes an important disease affecting cyprinids) replication. 87 Zhang et al 88 reported that neddylation of the polymerase basic protein 2 of influenza A virus reduces its stability and blocks the replication of influenza A virus. On the other hand, neddylation inhibition restores the restriction of human immunodeficiency virus by repressing the degradation of host restriction factors, a kind of cellular proteins inhibiting the replication of viruses at various stages of their life cycle.…”
Section: Neddylation In Infectionmentioning
confidence: 99%
“…First, neddylation is considered to control the amplification and replication of viruses. It is reported that blocking or silencing neddylation dramatically increased spring viremia of carp virus (an ssRNA virus that causes an important disease affecting cyprinids) replication 87 . Zhang et al 88 reported that neddylation of the polymerase basic protein 2 of influenza A virus reduces its stability and blocks the replication of influenza A virus.…”
Section: Neddylation Emerges As a Regulator Of Immune‐mediated Diseasesmentioning
confidence: 99%